Segmentasi Pelanggan Klinik Dokter Hewan Berbasis Algoritma K-Means dan Model RFM - Andikha; Rafi Dio; Meylia Vivi Putri; Dwila Sempi Yusiani; Berta Erwin SLAM; Adyk Marga Raharja; Rifaldi Herikson (Fakultas Teknik Universitas Ibnu Sina, 2025)
This study aims to segment customers of a veterinary clinic using a combination of Recency, Frequency, Monetary (RFM) analysis and the K-Means clustering algorithm. Transactional data from December 2024 to April 2025 were processed to generate key customer features, followed by min-max normalization to ensure comparability across variables. The segmentation was conducted in AI Studio 2025, with cluster quality evaluated using cluster distance performance and Davies-Bouldin Index. The analysis resulted in four distinct customer segments: the majority were passive customers with low transaction frequency and spending, while a smaller group showed high purchasing activity and made a significant economic contribution. This study demonstrates the effectiveness of automated data mining tools in uncovering meaningful customer profiles in a veterinary service context. The results provide a practical basis for targeted marketing, customer retention strategies, and service improvement in veterinary clinics. This approach offers valuable insights for data-driven decision making and represents a novelty for veterinary service management in Indonesia. Keywords: Customer Segmentation, RFM Analysis, K-Means Clustering, Veterinary Clinic, Data Mining.